2017
DOI: 10.1093/neuonc/nox207
|View full text |Cite
|
Sign up to set email alerts
|

Targeting different domains of gap junction protein to control malignant glioma

Abstract: A rational treatment strategy for glioma, the most common primary central nervous system tumor, should focus on early invasive growth and resistance to current therapeutics. Connexin 43 (Cx43), a gap junction protein, plays important roles not only in the development of the central nervous system and but also in the progression of glioma. The different structural domains of Cx43, including extracellular loops, transmembrane domains, and an intracellular carboxyl terminal, have distinct functions in the invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 97 publications
0
14
0
Order By: Relevance
“…Importantly, the opening and closing of GJCs or Hcs depend on their response to stimuli such as other cellular membrane channels [ 35 ]. Connexin proteins are the necessary components of GJCs and Hcs, and Cx43 is one of the most abundant members of the connexin protein family [ 36 ]. In recent years, studies have indicated that Cx43-containing GJCs and Hcs are the main cellular adhesion channels in astrocytes and maintain homeostasis of the neural microenvironment [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the opening and closing of GJCs or Hcs depend on their response to stimuli such as other cellular membrane channels [ 35 ]. Connexin proteins are the necessary components of GJCs and Hcs, and Cx43 is one of the most abundant members of the connexin protein family [ 36 ]. In recent years, studies have indicated that Cx43-containing GJCs and Hcs are the main cellular adhesion channels in astrocytes and maintain homeostasis of the neural microenvironment [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be determined if these peptides have utility in overcoming chemotherapeutic resistance in various stages or subsets of GBM cells or GSCs. An alternative strategy may involve the use of monoclonal antibodies designed against the extracellular domain of Cx43 to inhibit the connexon structure, alter GJIC and hemichannel activity, inhibit glioma invasion, and/or overcome chemoresistance (discussed in [63 • ]).…”
Section: Therapeutic Opportunity For Connexin43 Peptidomimeticsmentioning
confidence: 99%
“…The Cx43 C-terminus interacts with a number of signaling molecules including c-Src, protein kinase C, AKT serine/threonine kinase, and mitogen-activated protein kinase to name a few (reviewed in [63 • ]). These interactions can also affect the phosphorylation status of Cx43 and consequently regulate its degradation, subcellular localization, and channel assembly processes, in addition to potentially mediating GBM resistance to TMZ [64,65].…”
Section: Therapeutic Opportunity For Connexin43 Peptidomimeticsmentioning
confidence: 99%
“…Importantly,the opening and closing of GJCs or Hcs depend on the response to stimuli such as other cellular membrane channels [31]. Connexin proteins are the necessary components of GJCs and Hcs, and Cx43 is one of the most abundant members of the connexin protein family [32]. In recent years, studies have indicated that Cx43-containing GJCs and Hcs are the main cell adhesion channels in astrocytes and maintain the homeostasis of the neural microenvironment in the CNS [10].…”
Section: Discussionmentioning
confidence: 99%